166 Cardiovascular magnetic resonance (CMR) tagging identifies differential ventricular remodelling in patients with bicuspid vs tricuspid aortic valve disease. (9th June 2011) - Bull, S; Suttie, J; Blundell, N; Francis, J M; Karamitsos, T D; Pitcher, A; D'Arcy, J; Prendergast, B; Neubauer, S; Myerson, S G
Abstract : Background: Bicuspid aortic valves (BAV) are a common inherited abnormality with a very high rate of adverse cardiac events at an earlier age than tricuspid aortic valves (TAV). Risk stratification for moderate to severe aortic stenosis, in both bicuspid and tricuspid disease, remains a significant clinical challenge. It is unknown whether pathological left ventricular (LV) remodelling, a strong predictor of adverse cardiac events, differs between patients with bicuspid and tricuspid valvular disease with comparable transvalvular gradients. Cardiovascular magnetic resonance (CMR) tagging provides detailed characterisation of global and regional contractility, and is a powerful investigative tool in the assessment of myocardial disease. We therefore assessed left ventricular strain (using CMR tagging), valve morphology and LV hypertrophy in patients with bicuspid and tricuspid aortic valve disease matched for transvalvular gradient. Methods: 42 subjects were recruited in total: 24 patients with moderate to severe BAV (age 55 ±15 yrs, female 21%, peak trans-aortic velocity 3.1±0.6/ms, LV mass 172±48 g; SBP 127 ±14 mm Hg DBP 76 ±10 mm Hg) and 18 patients with velocity-matched TAV (age 74 ±6 years, female 28%, velocity 3.1±0.6/ ms, LV mass 147±27 g; SBP 136±17 mm Hg; DBP 79±7 mm Hg; Abstract 166 table 1 ). Patients were scanned using a 1.5 T Avanto scanner (Siemens Healthcare, Erlangen, Germany) and basal, mid-ventricular and apical short axis tagging images were acquired. Peak systolic global circumferential strain was calculated at each ventricular level using CimTag2D software v.7 (Auckland MRI Research Group, New Zealand). Results: Patients with BAV had significantly greater left ventricular hypertrophy (BAV 172 ±48 g vs TAV 147±27 g; p=0.04) despite similar degrees of valve stenosis. Peak systolic circumferential strain was lower (ie, reduced contractility) in patients with BAV than TAV (Basal BAV 20±3% vs TAV 22±3% P=0.04; Mid BAV 19 ± 2% vs TAV 21 ± 2% p=0.07; apical BAV 17±4% vs TAV 19±3%; p<0.04), despite the younger age and lower blood pressure. Conclusion: Ventricular remodelling differs between BAV and TAV patients with equivalent transvalvular gradients. BAV patients, despite being younger and having lower systolic blood pressure, have more severe hypertrophy and lower myocardial contractility. This finding may have implications for monitoring disease progression or more timely medical or surgical intervention in patients with BAV.